Extracellular vesicles released by LPS-stimulated spinal organotypic slices spread neuroinflammation into naïve slices through connexin43 hemichannel opening and astrocyte aberrant calcium dynamics - Memo, Christian; Parisse, Pietro; Amoriello, Roberta; Pachetti, Maria; Palandri, Anabela; Casalis, Loredana; Ballerini, Clara; Ballerini, Laura (Frontiers in Cellular Neuroscience, 2024)
Neuroinflammation is a hallmark of multiple neurodegenerative diseases, shared by all pathological processes which primarily impact on neurons, including Central Nervous System (CNS) injuries. In reactive CNS, activated glia releases extracellular vesicles (EVs), nanosized membranous particles known to play a key role in intercellular communication. EVs mediate neuroinflammatory responses and might exacerbate tissue deterioration, ultimately influencing neurodegenerative disease progression. In our study, we focus on CNS released small EVs (sEVs) and their impact on the biology of inflammatory environment. We address sEVs local signalling within the CNS tissue, in particular their involvement in inflammation spreading mechanism(s). sEVs are harvested from mouse organotypic spinal cord cultures, an in vitro model which features 3D complexity and retains spinal cord resident cells. We combine atomic force microscopy (AFM), nanoparticle tracking (NTA) and western blot (WB) analysis to validate the isolation and characterisation of sEVs. By confocal microscopy and live calcium imaging we monitor glial responses in naïve spinal slices when exposed to sEVs isolated from resting and LPS treated organ slices. We show that sEVs, only when released during LPS neuroinflammation, recruit naïve astrocytes in the neuroinflammation cycle and we propose that such recruitment be mediated by EVs hemichannel (HC) permeability.